Training And Guidance Of Hajj Manasik For Teenagers Of Al-Munazirin Mosque Pekanbaru City - Rahman (PT. Gudang Pustaka Cendekia, 2025)
This article is the result of community service regarding training and guidance for Hajj rituals for teenagers at the Al-Munazirin Mosque, Tampan District, Pekanbaru City.Hajj is a form of worship that involves deliberately visiting the Kaaba, to carry out certain acts of worship, or in other words, visiting certain places, at certain times, and carrying out certain acts of worship.. Al-Munazirin Mosque as a service location already has a mosque youth community, but is rarely given guidance and training, especially about the hajj rituals. For that, this activity needs to be carried out so that they can understand how. This service is carried out using a practical approach after providing material in this service activity. The results achieved after carrying out this hajj ritual training and guidance are that the teenagers of Al-Munazirin Mosque can be active again, so that they can develop their potential.